An integrated emergency response network : a solution to New Zealand's hazard environment : submitted as a requirement for the M. Phil. degree, Massey University - McGill, Mark C (Massey University, 1998)
By analysing the various response agencies presently operating in NZ and internationally, with an All Hazards approach in mind, is the development of a fully integrated emergency response structure the best option? Research would indicate that it would have positive outcomes. In a weighted comparison of the advantages, the opportunities and the disadvantages of merging the response agencies, the positive implications of merging outweigh the negative aspects. A main theme that arose from the research is the philosophical base of the emergency services and emergency management. The macro-philosophy and therefore the inherent value system of all the response agencies is to save life, protect property and render humanitarian services. If a merged response service enhances these values, while being cost effective and benefitting the public it should be pursued. Although it is human nature to protect what you have, it is essential for these organisations to take a holistic view of emergency management. There are other opportunities and advantages that exist that support the concept of a combined emergency response agency. Some of the perceived disadvantages are misnomers and the others can be eliminated if the right model is adopted and the necessary resources supplied. However one of the major problems highlighted by the research, were the barriers to change: people (perspective), politics (power) and patch protection (position). If there is to be a successful merger, the barriers must be neutralised. A possible approach is to merge the services and blend the cultures, thereby creating a perceived, singular, unified social identity. Those involved in the new organisation must feel part of this culture and be able to categorise themselves as being in the group of integrated response professionals. There has to be transference of expertise from the existing agencies to the new agency in such a way that a holistic multi-disciplinary response organisation is generated and guaranteed. Field notes indicate that any change should be open change, a change based on the core values of emergency management and not political ideology. In addition, those who are going to use the operational systems, the emergency response teams, should develop them. This is very important for success in the initial phases, along with the appropriate training to new and existing personnel. To minimise prejudice in system development the change process should be lead by a transitional management team. This team must have an international perspective with a sound knowledge base in the emergency management field, social psychology and team development. The aim is to evolve through from a multi-disciplinary team concept, to a trans-disciplinary and trans-cultural (social identity) response agency.
Keywords: Emergency Management; Emergency response